Diseño editorial y el aprendizaje en la alfabetización de mujeres indígenas en la parroquia Atahualpa de Ambato - Gamboa Freire, Stephanie Salomé (2023)
Currently, according to the National Institute of Statistics and Census (INEC), illiteracy rates in Ecuador have not decreased, since adult literacy is seen only as an option, but not as something necessary for development and to improve the quality of life. Therefore, the objective of this research is to analyze the editorial design and its relationship with the literacy learning of indigenous women in the parish of Atahualpa in the city of Ambato, through technical validation instruments that allow analyzing the variables. For this, a mixed approach was used with a deductive and inductive methodology to analyze theories and concepts, where solutions are proposed, the research modality used was bibliographic documentary, and for the collection of information the tools of convenience survey and interviews were used, the first one applied to 157 women of Atahualpa parish and the second one to editorial design professionals and teachers in education. As a result, editorial and educational parameters were obtained for the development of the proposal, which consists of establishing an editorial layout guide that includes the layout of headlines, text bodies and images in an educational text to support the learning process for illiterate people.